Perlindungan Hukum bagi Konsumen terhadap Produk Makanan Impor Latiao Asal Cina di Indonesia yang Berbahaya bagi Kesehatan - Afrisya Rahmany (Pusat Riset dan Inovasi Nasional, 2025)
Globalization has increased consumption of imported products in Indonesia, including snacks such as Latiao from China. However, a number of cases of poisoning due to consumption of Latiao show that this product can endanger consumers' health. This research aims to analyze consumer protection regulations in Law no. 8 of 1999 as well as the government's role in handling the circulation of dangerous imported products. The research method used is doctrinal legal research with a statutory approach and case studies. The research results show that even though consumer protection regulations are in place, weaknesses in supervision mean that there are still dangerous products circulating on the market. BPOM and related agencies have taken steps such as product recalls and investigations into dangerous ingredients, but supervision needs to be tightened. Synergy is needed between the government, business actors and the community to ensure food safety and increase consumer awareness of their rights